Historical Tools of Anthropometric Facial Assessment: A Systematic Raw Data Analysis on the Applicability of the Neoclassical Canons and Golden Ratio. (13th September 2021) - Khoshab, Nima; Donnelly, Megan R; Sayadi, Lohrasb R; Vyas, Raj M; Banyard, Derek A
Abstract: Background: The fundamental tenets of facial aesthetic surgery education have not changed in centuries. Research is beginning to demonstrate that the Neoclassical Canons and the Golden Ratio, Phi, have limited utilization in populations other than those of White European extraction. Objectives: The purpose of this study was to analyze comparable raw data in the literature to determine (1) if there is interethnic variability in Neoclassical Canon and Phi measurements, and (2) if the measurements in these representative samples differ from the "ideal." Methods: A PubMed/Scopus search was performed. Manuscripts with raw data and individuals aged ≥16 were included. Measurements were extracted and employed to calculate the Neoclassical Canons and Phi . One-way analysis of variance (ANOVA) tests were conducted to compare mean measurements across 6 ethnic groups ( P < 0.05). Results: Twenty-seven articles were included. Every continent was represented except Antarctica and Australia. Men were less commonly studied than women. Participant ages ranged from 16 to 56. Averaged Canons 2, 6-8 measurements had significant interethnic differences in males, whereas Canons 5-8 had significant differences across ethnicities in females. For men, there was significant interethnic variability in measurements of Phi 2, 5, 8, 10, and 17. For women, Phi 1, 2, 5, 8, 10, and 17 varied across ethnicities. No ethnic/gender group showed consistent approximation of the "ideal" for both the Neoclassical Canons and Phi . Conclusions: Today, the utility of the Neoclassical Canons and Phi is limited. It is incumbent on our field to systematically study and define the anthropometric measures that define the "ideal."